IMPROVING TEACHERS' CREATIVITY IN TEACHING DURING THE COVID-19 PANDEMIC THROUGH ASSIGNMENT METHODS AT SLB NEGERI PEMBINA PEKANBARU - Yasni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Based on the results of pre-research observations conducted at SLB Negeri Pembina Pekanbaru, several problems were found, namely: some teachers were not able to apply online learning at home due to limitations in technology. Then, many teachers applied the learning model containing many assignments without paying attention to the situation and conditions during this covid-19 outbreak. Learning became monotonous. By using creative learning model that was fun, the children's character and creativity could be fostered. Giving too much material and tiring children made the children lose their motivation for learning. The type of this research was school action research with a sample of 34 teachers at SLB Pembina Pekanbaru. Based on the results of the analysis and discussion, it was concluded that the teachers’ creativity in teaching increased through the assignment method. Under these conditions, the level of teacher acceptance increased. The comparison of aspects of teachers’ creativity in teaching through the assignment method in cycle I and II increased from 58.8% to 75.1%.